Critical methodological assessment of the distraction distance used for evaluating room acoustic quality of open-plan offices. (November 2018) - Cabrera, Densil; Yadav, Manuj; Protheroe, Daniel
Graphical abstract: Highlights: STI calculation method affects distraction distance ( r D ) of open-plan offices. Alternative speech spectra affect r D, but not speech SPL metrics in ISO 3382-3. r D is not affected by IEC 60268-16 male vs. female weights in STI calculation. Older STI models produce large changes in r D compared to the current STI standard. Auditory spectral masking can be introduced without any disruption to r D values. Abstract: ISO 3382-3, the international standard for evaluating the acoustics of open-plan offices, includes metrics based on measuring spatial decay, over workstations, of speech sound pressure level, and speech intelligibility. The speech intelligibility metrics, out of which distraction distance ( r D ) has recently been shown to be most useful, are derived from speech transmission index (STI) calculations. This study examines how the ISO 3382-3 metrics, especially r D, are affected by certain aspects of STI calculation, by using acoustic measurements of 20 offices. Results show that r D values calculated using ISO 3382-3 speech spectrum were significantly different to those calculated using other standard and proposed speech spectra. The choice of standard octave-band transmission index weights, e.g., male/female, used in standard STI calculation as per IEC 60268-16 (2011), did not significantly affect r D values. However, compared to the standard STI calculation, the pre-standard weights from the STI model from 1985 that is used in some important studies cited in ISO 3382-3 yielded much shorter r D values; RASTI yielded an increase in r D of less than 1 m; whereas STIPA (IEC 60268-16: 2011) did not affect r D . The effect of auditory spectral masking in standard STI calculation was negligible overall, but there were cases where the auditory masking reduced r D by up to 0.5 m. The effects of speech spectrum on two other relevant metrics in ISO 3382-3, namely spatial decay rate of speech, and A-weighted sound pressure level of speech at 4 m distance, were not significant. Overall, sensitivities of r D to several aspects of STI calculation are highlighted, which should contribute to the interpretation of studies that informed ISO 3382-3 development, support the current implied practice of using male STI weights for genderless speech in the calculation of r D, and provide guidance on potential refinements.